Enhancing properties of polyvinyl alcohol film using sorghum starch nanocrystals – A cost effective filler from natural source - Kumar, S. Vasantha; Sajeevkumar, V. A.; George, Johnsy; Kumar, Sunny (Defence Life Science Journal, 2017)
Poly Vinyl Alcohol (PVA) nanocomposite films with Sorghum Starch Nanocrystals (SSN) were prepared by incorporating various concentrations of SSN in PVA. SSN was isolated using acid hydrolysis of sorghum starch. The morphological studies of SSN using Atomic Force Microscopy (AFM) revealed that the particle size varied from 65 to 68 nm. The mechanical properties of PVA-SSN nanocomposite films indicated an improvement in tensile strength and percentage elongation at break when compared to that of PVA films. This can be attributed to the stronger interaction of PVA with SSN due to hydrogen bonding. Besides this, PVA-SSN nanocomposite films also exhibited good thermal properties. Thus, the use of SSN (a cost effective filler from natural source) imparted superior properties to the PVA nanocomposite films, which will be beneficial for applications such as food packaging.